PENERAPAN STRATEGI PEMBELAJARAN AKTIF FORMASI REGU TEMBAK UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STOIKIOMETRI KELAS X IPA SMAN 10 PEKANBARU - Desy Mayasari; Herdini Herdini; R. Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purposes of research are to know the improvement of student learning achievement and value of influence by implementing learning strategy the firing line subject in the class X IPA SMAN 10 Pekanbaru. This research is experimental research using Design Randomized Control Group Pretest-Posttest. The research sample consisted two class, class X IPA 3 as experiment class and class X IPA 4 as control class that has tested by normality test using Liliefors test and homogeneity test using equality of two average test. Hypothesis was done by using test-t right side. Research result shown that the implementation of learning strategy the firing line can improve student learning achievement on the stoichiometry subject where tarithmetic = 2,18 > ttable = 1,67 with value of its influence to student learning achievement is 0,71.Key Words : Learning strategy the firing line, Learning Achievement, stoichiometry